Sumber Daya Manusia pada Instalasi Alat Kesehatan (Alkes) Di RSUD Kota Dumai Tahun 2021 - Kamille Zola; Aldiga Rienti Abidin; Herman M Purwonegoro (Universitas Batanghari Jambi, 2022)
Every hospital, both government and private, is obliged to provide safe, quality, anti-discriminatory and effective health services by prioritizing the interests of patients in accordance with hospital service standards. The quality of service in a hospital is not only determined by human resources who are experts in their fields but also supported by the facilities of medical equipment in the hospital. This is very beneficial because it can minimize invasive procedures, so that complications and risks due to medical procedures can be reduced. Dumai City Hospital The supply of medical equipment is still lacking and incomplete according to existing guidelines, which can hinder the smoothness of services provided to patients. This minimal equipment greatly affects the quality of services provided including patient waiting time which becomes quite long. The purpose of this study is to apply the concepts and theories of hospital management to solve problems that exist in the installation of medical devices at the Dumai City Hospital, to identify resource requirements human and medical device problems based on real situation analysis at the Dumai City Hospital Medical Device Installation. This study uses a qualitative method with a rapid assessment procedure research design. The technique of taking informants is purposive sampling, namely the key informant is the head of the medical device installation and the main informant is the person in charge of medical medical devices. The data collection technique was carried out by in-depth interviews, document review and observation. Some of the problems found in the nursing committee unit using the ultrasound technique were found to be the priority of the problem, the lack of staff and the not yet optimal career development program for medical device installation officers. Alternative problem solving that can be done is planning to recruit new officers to manage the repair and maintenance of medical devices, determine the rules and sanctions given if there are officers who do not carry out their duties properly where the repair and maintenance of medical devices is a very important unit in health services, planning application procurement proposals to arrange repair and maintenance schedules that are integrated with SIMRS, making standard SOPs for medical device installations, planning training / technical guidance for medical device installation officers.